PENGEMBANGAN MEDIA PEMBELAJARAN MARGALA UNTUK MENGENALKAN MULTICULTURAL PADA ANAK USIA DINI - agustina, winarti (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2022)
Abstract The objectivity of this research is to develop technology-based learning media to introduce multiculturalism to early childhood. The research methodology used is Research & Development (R&D) with the Borg and Gall model. This media has conducted trials on three media experts who are competent in their fields. The media feasibility results obtained 87.13 with very feasible criteria. Keywords: Learning Media, Multicultural, Early Childhood